Pesantren dan Dakwah Lingkungan (Studi Pemikiran dan Gerakan TGH. Muhammad Sibawaihi Mutawalli Pimpinan Pesantren Darul Yatama wal Masakin Jerowaru Lombok Timur) - S. Ali Jadid Al Idrus (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study aims to determine the thinking and movement of TGH. Muhammad Sibawaihii Mutawalli Yahya Al-Kalimi, the leader of the Darul Yatama wal Masakin Islamic Boarding School, Jerowaru, East Lombok, regarding environmental issues as stated in his teaching points, works, as well as sustainable activities or movements and is contained in the educational curriculum in the Islamic boarding school environment. This research is a field research as a form of qualitative research with an interdisciplinary approach that is adapted. Collecting data through field observations, documentation, literature studies and interviews with related parties within the Islamic Boarding School, both families, educators, students, communities, and figures who are directly involved. This study concludes: first, environmental da'wah has become a movement as a result of TGH's thinking. Muhammad Sibawaihi Mutawalli Yahya Al-Kalimi. Second, reforestation, conservation, cultivation, animal husbandry and fisheries bring Islamic boarding schools into the category of environmental-based boarding schools. Third, environmental activities involve students and the community, so that it can be categorized as a participatory-based Islamic boarding school tradition.